Iron and Ferritin Levels in the Serum and Milk of Bovine Leukemia Virus-Infected Dairy Cows - Schnell, Star A.; Ohtsuka, Hiromichi; Kakinuma, Seiichi; Yoshikawa, Yasunaga; Watanabe, Kiyotaka; Orino, Koichi (Frontiers in Veterinary Science, 2015)
Iron metabolism was examined in 15 bovine leukemia virus (BLV) -infected dairy cows (2.6-7.8 years old). BLV infection was detected by measuring serum antibody titer against BLV virus antigen (gp51). The anti-BLV antibody titers of the BLV-infected cows were significantly higher in serum than in milk; a single serum-positive animal lacked detectable anti-BLV antibodies in its milk. Iron and ferritin concentrations also were significantly higher in serum than in milk. Although most of the BLV-infected dairy cows had past or present anamneses (such as inflammatory diseases, including intramammary infection), the milk ferritin concentrations of the infected cows were significantly lower than those of normal cows; serum ferritin concentrations did not differ significantly between these two groups. The anti-BLV antibody titers in milk samples showed significant correlation with serum iron concentrations. These results suggest that BLV infection affects iron homeostasis through iron metabolism in the dairy cow mammary gland.